Pengaruh Budaya Organisasi dan Employee Engagement Terhadap Kinerja Karyawan PT. Pos Indonesia (Persero) Cabang Baturaja (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
The Influence of Organizational Culture and Employees’ Engagement on Employees’ Performance at PT. Pos Indonesia (Persero) Baturaja Branch. This study discusses the Influence of Organizational Culture and Employees’ Engagement on Employees’ Performance of PT. Pos Indonesia (Persero) Baturaja Branch. The population in this study were 30 employees of PT. Pos Indonesia (Persero) Baturaja Branch. The analytical method used is quantitative method using Multiple Linear Regression analysis tool. The results of the analysis explain that the t-count for each variable of Organizational Culture (X1) is 4.458 and Employees’ Engagement (X2) is 3.622, which is greater than the t-table value of 2.052 which states that all variables have a significant influence on Employees’ Performance at PT. Pos Indonesia (Persero) Baturaja Branch. The calculated F value of 91.749 is greater than the F table of 3.35 which states that together Organizational Culture and Employees’ Engagement have a significant influence on Employees’ Performance at PT. Pos Indonesia (Persero) Baturaja Branch. The value of the coefficient of determination (R Square) of 0.872 means that in this case the contribution of the influence of Organizational Culture and Employee Engagement on Employees’ Performance is 87.2%, while the remaining 12.8% is influenced by other variables outside of the variables included in the model. This study, namely work motivation, responsibility, work discipline and incentives (Sedarmayanti, 2017: 228).